2023
DOI: 10.7759/cureus.35500
|View full text |Cite
|
Sign up to set email alerts
|

Ossified Superficial Infrapatellar Bursa: A Case Report

Abstract: Bursitis, though treatable conservatively, very rarely can have ossification and calcification in its substance which requires surgical intervention. The patient should be investigated for any coexisting metabolic bone disorders before proceeding with surgical intervention. The excision biopsy of such a specimen has to be examined histopathologically to rule out any neoplastic etiology. We present an adult male with a painful lump over the tibial tuberosity and its management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Patients with bursitis are typically treated conservatively using methods, such as cold therapy, activity modification, and nonsteroidal anti-inflammatory drugs [6]. If necessary, lidocaine and corticosteroids can be injected to treat inflammatory areas directly, and surgical treatments, such as debridement or excision, might be required if infection is suspected or not alleviated by conservative treatment [7,8]. To date, only a few studies have reported the effectiveness of Korean medicine treatments for infrapatellar bursitis.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with bursitis are typically treated conservatively using methods, such as cold therapy, activity modification, and nonsteroidal anti-inflammatory drugs [6]. If necessary, lidocaine and corticosteroids can be injected to treat inflammatory areas directly, and surgical treatments, such as debridement or excision, might be required if infection is suspected or not alleviated by conservative treatment [7,8]. To date, only a few studies have reported the effectiveness of Korean medicine treatments for infrapatellar bursitis.…”
Section: Introductionmentioning
confidence: 99%